PRINSIP- PRINSIP KESOPANAN DALAM FILM DEAD POETS SOCIETY KARYA THOM SCHULMAN (SUATU KAJIAN PRAGMATIK) - DJIKOAN, RAFIKA; JANSEN, FRIEDA TH.; MANUS, JEANE ANGELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled Prinsip-prinsip Kesopanan dalam Film Dead Poets Society Karya Thom Schulman : Suatu Analisis Pragmatik focuses on maxim related to the politeness principles. The aims of this research are to identify, classify and analyze the politeness principles and their functions in Dead Poets Society movie. The method of this research is descriptive method. The descriptive method is a method that used to find the elements and characteristics of a phenomenon. This method starts from collecting data, analyzing data, interpreting data. The data are collected through conversation among characters, classify and analyze them according to the concept of Leech (1983). The result shows that there are six maxims of politeness and their function applied by the characters in their dialogues. Those are the tact maxim, the genorisity maxim, the approbation maxim, the modesty maxim, the agremeent maxim, and the sympathy maxim. It is expected that this research will help students and readers in learning pragmatic, especially on politeness principles. Keywords : Politeness Principles, Pragmatic Analysis, Dead Poets Society Movie